Multi-wall carbon nanotubes tailored eutectic composites for solar energy harvesting - Jacob, Jeeja; Pandey, Adarsh Kumar; Nasrudin, Abd Rahim; Selvaraj, Jeyraj; Paul Nadakkal, John (Elsevier Ltd, 2024)
Carbonaceous thermal energy storage involving PCMs has gained an increasing research interest owing to their higher thermal conductivity and energy storage density. The current work analyses the thermophysical properties of a nano-enhanced eutectic phase change material (NeUPCM) laden with different concentrations (ranges from 0 wt% - 0.7 wt%) of multi-wall carbon nanotube (MWCNT). Paraffin wax-palmitic acid (PW-PA) binary eutectic was produced initially by facile melt blending, and then MWCNTs were doped via standard two-step nanocomposite synthesis protocol. Nanocomposites showed a slower decomposition rate, and the thermal resistance index improved. MWCNT enhance the thermal conductivity of the eutectic base (140 %), which reaches a maximum value of 0.619 W/(m•K) for 0.5 wt% loadings, and the maximum increment of 13.2 % of latent heat was noted for 0.7 wt% loading of MWCNT (which is having a melting temperature of 53 °C). The sample doped with 0.5 wt% MWCNT(C3) showed the highest thermal effusivity. The NeUPCMs also displayed improved photothermal performance and solar absorptivity. Corrosion analysis against copper revealed that the composite is suitable for long-term usage. The NeUPCMs maintained good reliability even after 500 melt-freeze cycles. In short, the proposed NeUPCMs hold significant potential to be employed for thermal energy storage purposes.